Synthesis of analogs of the radiation mitigator JP4-039 and visualization of BODIPY derivatives in mitochondria - Frantz, Marie-Céline (2013)
JP4-039 is a lead structure in a series of nitroxide conjugates that are capable of accumulating in mitochondria and scavenging reactive oxygen species (ROS). To explore structure-activity relationships (SAR), new analogs with variable nitroxide moieties were prepared. Furthermore, fluorophore-tagged analogs were synthesized and provided the opportunity for visualization in mitochondria. All analogs were tested for radioprotective and radiomitigative effects in 32Dcl3 cells.